The application of biotechnology to industrial sustainability. (Sustainable development., 2001)
"Biotechnology can help improve the environmental friendliness of industrial activities and lower both capital expenditure and operating costs. It can also help reduce raw material and energy inputs and waste"--Page [4] of cover.